Fuzzy Dynamic Scheduling of Multi-loop NCS - Fang He; Jiajia Pang; Qiang Wang; Zhijie Zhang (Institute of Advanced Engineering and Science, 2013)
There are more problems of network data transmission in multi-loop NCS than in single loop NCS. It maybe lead to that one or more of closed-loop systems become unstable in multi-loop NCS. In order to solve this problem, a novel algorithm of fuzzy dynamic scheduling for multi-loop NCS is put forward in this paper. Firstly, the requirement of the sampling period of NCS is discussed. The necessity of dynamic scheduling for multi-loop NCS is analyzed. And then, the algorithm of fuzzy dynamic scheduling for multi-loop NCS is proposed. The idea is described form three parts.The principle of fuzzy dynamic scheduling is analyzed. The fuzzy controller is designed. The fuzzy dynamic scheduler is constructed. Finally, the simulation model of a multi-loop NCS with fuzzy dynamic scheduler is set up using TrueTime software. The relevant analysis of simulation is given. The result of study can prove that the performance of each closed control loop based on the same network platform is improved by adding fuzzy dynamic scheduler in the multi-loop NCS. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2453